High‐copy sequences reveal distinct evolution of the rye B chromosome. Issue 2 (24th April 2013) - Klemme, Sonja; Banaei‐Moghaddam, Ali Mohammad; Macas, Jiri; Wicker, Thomas; Novák, Petr; Houben, Andreas
Summary: B chromosomes (Bs) are supernumerary chromosomes that vary in number among individuals of the same species. Because of their dispensable nature, their non‐Mendelian inheritance and their origin from A chromosomes (As), one might assume that Bs followed a different evolutionary pathway from As, this being reflected in differences in their high‐copy DNA constitution. We provide detailed insight into the composition and distribution of rye ( Secale cereale ) B‐located high‐copy sequences. A‐ and B‐specific high‐copy sequences were identified in silico . Mobile elements and satellite sequences were verified by fluorescence in situ hybridization (FISH). Replication was analyzed via EdU incorporation. Although most repeats are similarly distributed along As and Bs, several transposons are either amplified or depleted on the B. An accumulation of B‐enriched satellites was found mostly in the nondisjunction control region of the B, which is transcriptionally active and late‐replicating. All B‐enriched sequences are not unique to the B but are also present in other Secale species, suggesting the origin of the B from As of the same genus. Our findings highlight the differences between As and Bs. Although Bs originated from As, they have since taken a separate evolutionary pathway.